Revitalization of Indonesian criminal law through the acknowledgment of living law: An investigation of the Sigajang Laleng Lipa’ customary law - Harefa, Beniharmoni; Fernando, Zico Junius; Maharani, Asari Suci; Anditya, Ariesta Wibisono; Humana, Sri (Jurnal Hukum Novelty, 2024)
Introduction to the Problem: The research article examines the Sigajang Laleng Lipa’ tradition in South Sulawesi’s Bugis community as a "living law" under Indonesia's new criminal code, specifically Article 2. The tradition’s violent nature, often leading to fatal outcomes, may conflict with principles in the updated code. Purpose/Study Objectives: The primary objective of this study is to conduct an analysis of criminal law regulations in Indonesia regarding the Sigajang Laleng Lipa’ tradition and assess its alignment with Article 2 of the new Indonesian Criminal Code. The study aims to understand whether this traditional conflict resolution mechanism meets the legal standards set out in the new code, especially concerning the concept of living law. Design/Methodology/Approach: This research employs a normative juridical method with a statutory and conceptual approach to legal recognition in Indonesian criminal law. Secondary data, gathered through literature sources like books and journals, facilitates an in-depth examination of the Sigajang Laleng Lipa’ tradition and the Indonesian criminal code. The doctrine of proportionality guides this study, emphasizing that punishment should match the crime to ensure justice and prevent excessive penalties. Findings: The findings reveal that the Sigajang Laleng Lipa’ tradition, despite its historical and cultural significance in the Bugis community, involves violent practices that have led to fatal consequences. Moreover, it is observed that this tradition does not fulfil the criteria set forth in Article 2, Paragraph (2) of the new Criminal Code. This mismatch highlights a significant challenge in incorporating living law traditions into the modern legal framework of Indonesia. Due to its inconsistency with philosophical, juridical, and sociological principles, the tradition cannot be sustained. Consequently, its use as a punitive measure is unjustifiable, as it does not effectively achieve criminal justice objectives and provides minimal social benefit, lacking contribution to crime prevention efforts. Paper Type: Research Article